1980
DOI: 10.1007/bf02662051
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant for fats and oils from canary seed: Sterol and triterpene alcohol esters of caffeic acid

Abstract: Several kinds of seeds used as bird feed were extracted successively with hexane, ether and methanol. In the antioxidant test with extracts, the ether extract from canary seeds showed the highest activity. The antioxidant fraction separated from it by thin layer chromatography showed excellent activity for lard and sardine oil. The effective components were identified by gas chromatography and gas chromatography‐mass spectrometry of the hydrolyzed products as the esters of caffeic acid with cycloartenol, grami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

1984
1984
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…Canaryseeds contain high amounts of unsaturated fatty acids, which is advantageous for a healthy diet, but could make them prone to oxidation and rancidity. However, the presence of certain antioxidants in canaryseed oil, such as caffeic acid esters, could potentially reduce these detrimental effects [ 72 ]. Furthermore, Ben Salah, et al [ 73 ] reported health promoting activity in canaryseed oil, produced from a hairy Tunisian canaryseed variety, which demonstrated antioxidant, antibacterial, and antiacetylcholinesterase activity, which was largely attributed to the high total polyphenol content in the oil.…”
Section: Other Health Promoting Canaryseed Componentsmentioning
confidence: 99%
“…Canaryseeds contain high amounts of unsaturated fatty acids, which is advantageous for a healthy diet, but could make them prone to oxidation and rancidity. However, the presence of certain antioxidants in canaryseed oil, such as caffeic acid esters, could potentially reduce these detrimental effects [ 72 ]. Furthermore, Ben Salah, et al [ 73 ] reported health promoting activity in canaryseed oil, produced from a hairy Tunisian canaryseed variety, which demonstrated antioxidant, antibacterial, and antiacetylcholinesterase activity, which was largely attributed to the high total polyphenol content in the oil.…”
Section: Other Health Promoting Canaryseed Componentsmentioning
confidence: 99%
“…El ácido clorogénico es el ácido fenólico más abundante en las plantas y también el antioxidante más activo de este grupo. De la semilla del alpiste (Phalaris canariensis) se han aislado esteres del ácido cafeico con esteróles y triterpenos (Takagi, 1980). Los ácidos grasos de esta semilla son muy insaturados y se ha sugerido que estos esteres los protegen de la oxidación.…”
Section: áCidos Cinámicosunclassified
“…The mixture of steryl ferulates: 4,4′-dimethyl sterol esters 24-methylenecycloartanyl ferulate and cycloartenyl ferulate naturally present in rice is known as γ-oryzanol, while desmethylsterols (sitosterol, campesterol and their saturated forms, stanols) are dominated in other cereals [ 6 , 7 , 8 , 9 , 10 ]. Moreover, steryl caffeates (campesterol and cycloartenol caffeates) as well as steryl sinapate (24-methylenecholesteryl sinapate) were found in various rice varieties [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%